2012
DOI: 10.1017/s0714980812000207
|View full text |Cite
|
Sign up to set email alerts
|

Formal Dementia Care among First Nations in Southwestern Ontario

Abstract: This article explores how dementia care is provided to First Nations communities in southwestern Ontario. Data were collected through in-depth interviews with health care providers and analysed using a constructivist grounded-theory methodology. Two interrelated frameworks for understanding dementia care were identified: a care delivery framework and a knowledge framework. The care delivery framework identified care goals, care elements being provided, care barriers, and strategies and solutions to deliver car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…Commonalities between the fi ndings of this study and other research on knowledge sharing within dementia care networks include the importance of developing trusting relationships among PWDs, their care partners, and HCPs (e.g., Finkelstein et al, 2012 ). Trusting relationships were developed through the use of strategies such as (a) having a supportive network of PWDs, care partners, and neighbours; (b) HCPs' approaches that were culturally sensitive and client and familycentred; (c) resolving confl ict; (d) continuity of care; and (e) sustaining community programs.…”
Section: Resultsmentioning
confidence: 66%
“…Commonalities between the fi ndings of this study and other research on knowledge sharing within dementia care networks include the importance of developing trusting relationships among PWDs, their care partners, and HCPs (e.g., Finkelstein et al, 2012 ). Trusting relationships were developed through the use of strategies such as (a) having a supportive network of PWDs, care partners, and neighbours; (b) HCPs' approaches that were culturally sensitive and client and familycentred; (c) resolving confl ict; (d) continuity of care; and (e) sustaining community programs.…”
Section: Resultsmentioning
confidence: 66%
“…Improving health literacy is thought to benefit both the individual and health system, in that it can improve selfmanagement, allowing Indigenous people to make sound health decisions and reduce the use of health services (Mitic and Rootman 2012). Research suggests that older Indigenous people may be accessing services quite late in their dementia journey and are not benefiting from early detection and intervention (Buchignani and Armstrong-Esther 1999;Finkelstein et al 2012;Henderson and Henderson 2002). The resultant fact sheets can serve to support those initial conversations between health care providers and Indigenous older adults and families concerned about memory loss and confusion; or, as a tool for individuals and families outside of the health system.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows a lack of basic dementia care resources in Canada, especially Indigenousspecific dementia care literature (Finkelstein et al 2012). Caregivers, older adults, nurses, personal support workers, and researchers often request Alzheimer's and age-related dementias health promotion materials targeted to the Indigenous peoples in Canada but none exist (Jacklin et al 2014b;2014cPace et al 2013.…”
mentioning
confidence: 99%
“…Our knowledge of how Indigenous peoples experience dementia is limited (Boss et al, 1995; Finkelstein, Forbes, & Richmond, 2012; Jacklin, Warry, Blind, Webkamigad, & Jones, 2017b). Most research with Indigenous peoples to date has found that the biomedical construct of dementia, in which dementia is perceived as a disease, is not well understood, and that often the illness is not viewed as problematic.…”
Section: Resultsmentioning
confidence: 99%